2014
DOI: 10.3168/jds.2013-6997
|View full text |Cite
|
Sign up to set email alerts
|

A study based on records taken at time of hoof trimming reveals a strong association between the IQ motif-containing GTPase-activating protein 1 (IQGAP1) gene and sole hemorrhage in Holstein cattle

Abstract: Feet and leg problems have a major effect on the well-being and lifespan of the dairy cow and thus are economically important to the dairy farmer. Apart from approaches using genetic selection for classical traits from conformation scoring, attempts for genetic improvement can be based either on records of individual disease cases or on records of disorder status at time of hoof trimming. In this study, 1,962 first-lactation cows were subjected to hoof trimming with an assessment of disorder status for sole he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 56 publications
1
17
1
Order By: Relevance
“…The IQ motif-containing GTPaseactivating protein 1 (IQGAP1) gene was found to have a strong association with sole hemorrhage in German Holstein cattle (Swalve et al, 2014). We did not detect any SNP on BTA21 at 22 Mb, where IQGAP1 is located.…”
Section: Comparison With Previous Qtl Studiesmentioning
confidence: 74%
See 1 more Smart Citation
“…The IQ motif-containing GTPaseactivating protein 1 (IQGAP1) gene was found to have a strong association with sole hemorrhage in German Holstein cattle (Swalve et al, 2014). We did not detect any SNP on BTA21 at 22 Mb, where IQGAP1 is located.…”
Section: Comparison With Previous Qtl Studiesmentioning
confidence: 74%
“…A few studies have detected QTL for some FLD, such as hoof trimming, lameness, and claw disorders (Buitenhuis et al, 2007;Swalve et al, 2014;van der Spek et al, 2015). However, genetic studies on feet and legs traits are limited due to a lack of recording in most countries.…”
Section: Introductionmentioning
confidence: 96%
“…A general consideration for the collection of health data is whether to diagnose only affected cows or to record whole cohorts of animals. Including complete contemporary groups has the benefit that affected and nonaffected cows contribute to the later analysis, which is particularly advantageous for association studies as shown by Swalve et al (2014). An example for an improved definition of an existing trait is the claw disorder dermatitis digitalis.…”
Section: Strategies For Phenotypingmentioning
confidence: 99%
“…Lameness is currently one of the most critical problems in dairy farming, affecting animal health and welfare [ 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Lameness is described as a clinical symptom, which is recognizable by a change in locomotion, usually associated with lesions of the pelvic limbs.…”
Section: Introductionmentioning
confidence: 99%
“…Lameness is described as a clinical symptom, which is recognizable by a change in locomotion, usually associated with lesions of the pelvic limbs. More than 90% of diagnosed lesions affect the distal part of the limb [ 11 , 13 , 15 , 16 , 17 , 18 , 19 , 20 ]; however, the resulting lesions are not only a welfare problem, but they also affect production and profit [ 8 , 14 , 15 , 19 , 21 , 22 ]. Dairy cows that are affected by limb diseases have lower dry matter intake and milk yield [ 3 , 4 , 9 , 10 , 11 , 14 , 16 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], reduced fertility [ 3 , 4 , 15 , 16 , 17 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], and they have an increased risk of culling [ 3 , 4 , 11 , 14 , 16 , 17 , 18 , 19 , ...…”
Section: Introductionmentioning
confidence: 99%